Respostas cardiorrespiratórias ao treinamento e destreinamento com kettlebell em mulheres jovens - Zimerer, Carla (2017)
The maximum oxygen consumption ( O2max) is a key parameter of cardiorespiratory fitness. Improvements in this parameter from the kettlebell training (KTB) can be obtained with the specificity of the cardiovascular and metabolic responses generated from the manipulation of variables, such as frequency, duration and training intensity. However, few studies investigated the effect of KTB training on cardiorespiratory fitness and based on these studies, it is difficult to discuss which type of training models are most effective to increase the O2max. In addition, it’s not known the effects of detraining and individualized prescription intensity models related to KTB. For this purpose, O2max values were obtained in three moments: before training (PRE), after training (POS) and after detraining (DES). Based on these assumptions, the aim of this study was to evaluate the effects of KTB training (10 weeks) and detraining (4 weeks) on the cardiopulmonary fitness in 15 young women. The KTB training was performed on three days of the week and the intensity of the sessions was prescribed individually. A significant increase in maximal oxygen consumption (8.1%) was found as a result of KTB training. No significant differences were found in O2max when the PRE and DES moments were compared. In conclusion, it was found that 10 weeks of high intensity KTB training were effective in promoting significant increase in maximal oxygen uptake in young women. The effect of this increase, however, was reversed after the shortterm detraining period (4 weeks).